Hybrid nanocomposites of nanostructured Co3O4 interfaced with reduced/nitrogen-doped graphene oxides for selective improvements in electrocatalytic and/or supercapacitive properties. Issue 53 (30th June 2017) - Hu, Sheng; Ribeiro, Erick L.; Davari, Seyyed Ali; Tian, Mengkun; Mukherjee, Dibyendu; Khomami, Bamin
Abstract : Hybrid nanocomposites (HNCs) of Co3 O4 nanoparticles/nanorods embedded in reduced/nitrogen-doped graphene oxide, manufactured via laser ablation synthesis in solution (LASiS), exhibit selective electrocatalytic/supercapacitive properties. Abstract : Performance enhancements in next-generation electrochemical energy storage/conversion devices require the design of new classes of nanomaterials that exhibit unique electrocatalytic and supercapacitive properties. To this end, we report the use of laser ablation synthesis in solution (LASiS) operated with cobalt as the target in graphene oxide (GO) solution in tandem with two different post-treatments to manufacture three kinds of hybrid nanocomposites (HNCs) namely, (1) Co3 O4 nanoparticle (NP)/reduced graphene oxide (rGO), (2) Co3 O4 nanorod (NR)/rGO, and (3) Co3 O4 NP/nitrogen-doped graphene oxide (NGO). FTIR and Raman spectroscopic studies indicate that both chemical and charge-driven interactions are partially responsible for embedding the Co3 O4 NPs/NRs into the various GO films. We tune the selective functionalities of the as-synthesized HNCs as oxygen reduction reaction (ORR) catalysts and/or supercapacitors by tailoring their structure–property relationships. Specifically, the nitrogen doping in the NP/NGO HNC samples promotes higher electron conductivity while hindering aggregation between 0D CoO NPs that are partially reshaped into Co3 O4 nanocubes due to induced surface strain energies. Our results indicate that such interfacial energetics and arrangements lead to superior ORR electrocatalytic activities. On the other hand, the interconnecting 1D nanostructures in the NR/rGO HNCs benefit charge transport and electrolyte diffusion at the electrode–electrolyte interfaces, thereby promoting their supercapacitive properties. The NP/rGO HNCs exhibit intermediate functionalities towards both ORR catalysis and supercapacitance.